Aus dem Nachlass Varnhagen's von Ense : Briefe von Chamisso, Gneisenau, Haugwitz, W. von Humboldt, Prinz Louis Ferdinand, Rahel, Rückert, L. Tieck u. a. / nebst Briefen, Anmerkungen und Notizen von Varnhagen von Ense. - Varnhagen von Ense, Karl August, 1785-1858. (Tufts University. Tisch Library., 2015)
1 online resource (2 volumes); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.